Synthesis and characterization of heteroatomdoped carbon nano-onions supported bimetallic nanoparticles for application in both direct alcohol and ammonia fuel cells - Sikeyi, Ludwe Luther (My University, 2024)
The pressing demand for inexpensive, highly active and operational stability electrocatalyst materials for direct alcohol fuel cells (DAFC) and direct ammonia fuel cells (AFC) has inspired remarkable research and growing interest in this field. The main pressing concerns related with the commercial use of these fuel cells (FCs) are their significant expense, low activity and the insufficient long-term stability of the commonly used Pt/C electrocatalysts due to facilitate the intrinsic slow kinetics for the alcohol and ammonia oxidation reaction. As such, the substitution of Pt/C with novel and more successful nanocatalyst materials is critical. The high activity and long-term operational stability of the nanocatalysts rely to a large extent upon the attributes and properties of the carbon support material. In this work, unique support materials were designed from onion-like carbon nanoparticles (OLCNs) for Pt and Pd catalysts to enhance their activity in FCs. OLCNs and the sulphur doped OLCNs were synthesized by a flame pyrolysis (FP) method to give p-OLCNs and S-OLCNs (S = 1.6 %) respectively. The synthesis of nitrogen doped (N-OLCNs) and oxygen functionalized nano-onions was achieved using chemical vapour deposition and reflux methods, respectively. Various Pd and Pt based electrocatalysts were then prepared for pristine, doped and functionalized OLNCs using a microwave-assisted synthesis method and their electrocatalytic activity was evaluated for the ethanol oxidation reaction (EOR). Based on a half-cell electrochemical investigation of the ethanol oxidation reaction in alkaline electrolyte, nitrogen and sulphur doped electrocatalysts demonstrated enhanced EOR catalytic activity and better stability, as well as fast electron transfer when compared to the equivalent undoped and commercial Pd/C electrocatalysts. To further explore the use of OLCNs as support material, bimetallic (Pd/Ag and Pd/Zn) electrocatalysts supported on N-OLCNs were prepared by a one pot synthesis method using sodium borohydride as a reducing agent. The Pd/NOLCN, Pd/Ag/N-OLCN, Pd/Zn/N-OLCN and Pd/C electrocatalysts were studied in iii the methanol oxidation reaction (MOR). The bimetallic (Pd/Ag/N-OLCN and Pd/Zn/N-OLCN) electrocatalysts exhibited superior anti-poisoning tolerance, better electrocatalytic stability and fast charge transfer resistance when compared to monometallic (Pd/N-OLCN and Pd/C) electrocatalysts in the methanol electrooxidation in alkaline media. The improved catalytic performance could be attributed to the strong metal–support interaction Overall, the FP method offered a facile synthesis route for the production of nanocarbons. The Pt or Pd nanoparticles supported on the surface of the modified OLCNs resulted in enhanced electrocatalytic activity in both alcohol and ammonia FCs..
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023
Keywords: Alcohol fuel cells; Ammonia fuel cells; Fuel cells